Analysis of Learning Projects in the Implementation of the Kurikulum Merdeka in Elementary Schools - Darmayanti, Vivi; Dewi, Naomi Dias Laksita; Arif, Moh. Badrus Sholeh (EDUCARE: Journal of Primary Education, 2023)
The Kurikulum Merdeka allows teachers to design educational and enjoyable learning experiences, with project-based learning being one of its most engaging and meaningful methods. This study aims to explore the types of projects commonly implemented by elementary school teachers under the Kurikulum Merdeka. Data were collected through questionnaires distributed to 20 elementary school teachers. The data were analyzed using a quantitative descriptive approach in the form of percentages. The findings reveal that the most frequently used project types are posters (45%), followed by interviews (20%), practicums (10%), concept maps (10%), and other activities such as making maps, performances, and comics (each at 5%).